Macroeconomic determinants of stock price volatility: Evidence from the Indonesia Stock Exchange - Aldiansyah, Aldiansyah; Christa, Usup Riassy; Syamsudin, Achmad (JSM: Jurnal Sains Manajemen, 2025)
This study investigates the effect of macroeconomic variables Gross Domestic Product (GDP) growth and inflation on stock price volatility in the Indonesia Stock Exchange (IDX) during the period 2018 to 2023. The motivation stems from Indonesia’s post-pandemic economic recovery and the need to understand how macroeconomic changes influence financial market dynamics. The research aims to determine whether GDP and inflation, individually or jointly, significantly impact the volatility of the Indonesia Composite Index (IHSG). Using a quantitative approach, secondary time-series data were analyzed through multiple linear regression using the Ordinary Least Squares (OLS) method. The model was tested for classical assumptions, including normality, multicollinearity, and autocorrelation, to ensure result validity. The findings reveal that GDP has a significant negative effect on IHSG volatility, suggesting that higher economic growth stabilizes market movements. In contrast, inflation was found to have no significant effect, implying that it may be already anticipated or offset by firm-level fundamentals and monetary policies. Moreover, the F-test result shows that GDP and inflation together do not have a significant simultaneous impact on stock price volatility. The model’s explanatory power remains moderate, indicating the need to consider other factors such as interest rates, exchange rates, and global shocks. This study recommends that policymakers prioritize sustained GDP growth as a strategy to maintain capital market stability, while investors are advised to monitor macroeconomic signals especially GDP when making investment decisions. Future research should integrate broader macro-financial variables and employ advanced modeling techniques to improve understanding of stock volatility in emerging markets like Indonesia.